Problematika Dakwah dan Da’i Perspektif Fathi Yakan (Studi Teks Kitab Musykilat Ad-Da’wah Wa Ad-Da’iyah) - Fatimah, Siti; Annafis, Lulu Al (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Agama Islam Mulia Astuti (STAIMAS) Wonogiri, 2024)
Da’wah is present as a solution to the problems of the people. But in fact, preaching is also a challenge for preachers. Not a few da’i who experience rejection when preaching I a sphere where the composition of society is heterogeneous. This library research-based research with a text study approach aims to analyze the problems of da’wah in the book Musykilat Ad-Da’wah wa Ad-Daiyah by Fathi Yakan. Data collection is done by documentation. The primary data source is the book Musykilat Ad-Da’wah wa Ad-Daiyah by Fathi Yakan. Secondary data sources were obtained fro relevant scientific literature. The results of the study show that the problem of da’wah has been inherent is the Islamic movement since the prophetic era. Even so, it does not erase the obligation of Muslim to preach according to their abilities. Therefore, despite facing various tests and challenges inherent in the development of Islam, both in the form of traditional and modern movements. For someone who wants to be involved in da’wah activities with the aim of encouraging goodness, it is important to adapt it to their abilities and capacities. However, the most important thing is to have good morals.